THE IMPACf OF BRAND IMAGE AND BRAND AWARENESS ON REPURCHASE INTENTION VIA PERCEIVED QUALITY - Siboro, Mindo Yumanda; Soesanto, Harry Seesaato (Faculty of Economics and Business Diponegoro University, 2015)
Nowadays. Tourism, one of the Indonesia commodities has been giving huge role in raising the Indonesia GDP. The number of the tourism in Indonesia is increasing significantly. Whereas, the number of the local visitors who came to Lake Toba (one of the biggestlourism place in Indonesia) increasing slowly. The aim of this research is to examine the factors that may influence tourist to visit Lake Toba. The study surveyed 185 visitors who came to Lake Toba. The survey period was from third week of July 2015 to fourth week of July 2015. The data analyses were conducted by confirmatory factor analysis and structural equation modeling. The results of the statistical analysis reflected that most of the visitors of Lake Toba are highly concern about Brand Image four times more than Brand Awareness. This study demonstrates that brand image and brand awareness positively affects perceived quality. moreover, perceived quality is the factors that influence the tourist to visit Lake Toba.